2011
DOI: 10.1002/app.35394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of silicone polyether additives as antifoams in crude oil

Abstract: It is common for crude oil from wells to be accompanied by gas and water because of the presence of natural surfactants in the oil that stabilize the associated water. This causes foaming during processing in gas/oil separators because of the constant agitation and shear forces, which reduce the efficiency of the process and require chemical control by the addition of defoaming additives, or antifoams. In this work, we evaluated the chemical and physicochemical properties of commercial antifoam products based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Surfactants based on polyether silicone of different polarities and molar masses were selected to act on the stabilization of the o/w nanoemulsions developed in this work. Previous study showed the high efficiency of these additives in the petroleum emulsions demulsification process, this factor being the preponderant that led to the choice of these compounds. Samples were called SP1, SP2, SP3, SP4, and characterization demonstrated in Table has been executed by the company providing the additives, Momentive, São Paulo‐Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Surfactants based on polyether silicone of different polarities and molar masses were selected to act on the stabilization of the o/w nanoemulsions developed in this work. Previous study showed the high efficiency of these additives in the petroleum emulsions demulsification process, this factor being the preponderant that led to the choice of these compounds. Samples were called SP1, SP2, SP3, SP4, and characterization demonstrated in Table has been executed by the company providing the additives, Momentive, São Paulo‐Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…The (o/w) nanoemulsions as defoamers for petroleum efficiency evaluation was executed based on the methodology developed in lab and utilized in previous work …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations